Blizzard showdown [large type] - McCoy, Shirlee (Alaska K-9 unit., 2021)
"After months of searching for Violet James, Gabriel Runyon and his K-9 partner finally track her down- just in time to rescue her from her ex-fiancé. Now they must safeguard the single mother and her newborn daughter. Leaving Violet's Alaskan hideout is the safest option, but with a winter storm rolling in, it's not just a murderer they have to escape."--Back cover.